DETERMINATION OF CRITERIA OF BREEDING OF CHILDREN OF LABOUR MIGRANTS - Hevchuk, Nataliia S. (Educological discourse, 2014)
The basic criteria of breeding of children of labour migrants are examined in the article; description of indexes of breeding of this category of children is given; the theoretical going near determination of concepts "education" and "breeding" is generalized; a diagnostic tool is presented by means of that the criteria of breeding of children of labour migrants are determined in the context of socialeducator work of general educational establishment.